Soil EC mapping system using veris 3100 at young oil palm area / Nurul Amirah Ahmad Zaki - Ahmad Zaki, Nurul Amirah (Faculty of Plantation and Agrotechnology, 2019)
Soil electrical conductivity (EC) is a measurement that links with the soil properties that will affect crop productivity. With advances in technology for precision agriculture, Veris Technologies introduce the on-the-go sensors for measuring level of Soil EC. The combination of sensor with EC help in improving our farming system. This study was conducted at Share Farm UiTM Jasin,Melaka in Young Oil Palm area and used to measure the level of EC. This implement (Veris 3100) connected along with Auto Pilot Tractor (New Holland TD575). It works together with GPS to get accurate location before it converted to map form. The collected data contain shallow and deep. Each data shows different amount of EC. Shallow measure from 0-30cm while Deep from 0-90cm and the data measure by millisiemens. Then do an interpolation by using kriging method by used ArcGIS. Function of this software to digitize the data to get it clearer. With the development of ArcGIS software, it improves our map from simply to fully functioning system. Based on the result, it shows that there no much different of EC in that area. Besides, the fact that sands have a low conductivity, silts have a medium conductivity and clays have a high conductivity.